Potensi Terapi Tertawa sebagai Terapi Hipertensi - Fakhira Arminda (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2020)
Laughter therapy is a therapy to achieve joy, pleasure, happiness, in the heart that is issued through the mouth in the form of laughter, smiles that decorate the face, loose and happy conscience, blood circulation that can be adapted to disease, health care, can also be help emphasize. It has been found a long time ago, in the medical field itself the use of laughter therapy as a therapy for disease is very rare. As explained earlier, therapy can relieve stress, whereas stress itself is highly related to hypertension. Hypertension is a problem related to negative stress or pressure. Psychologically, logically, and psychologically emphasize the results of responses to problems involving a person. Because stress is related to perception, complementing clinical management requires the management of non-pharmacology, especially hypertensive patients by trying laughter therapy.